Student Strategies for Collaborative Disciplinary Decision Making in an Elementary Engineering Teaching Experiment - Batrouny, Nicole. (Tufts University. Tisch Library., 2019)
Elementary engineering education is implemented in a wide variety of ways, from after-school programs to student-led outreach to fully integrated, standards-based classroom instruction. In all of these, students are expected to perform complex practices of engineering while (usually) working in collaborative teams, which presents a slew of challenges to novice learners. To explore the sources of and potential tools for navigating these challenges, we designed a teaching experiment to support students in decision-making and groupwork. In this thesis I 1) describe the theory and instructional reasoning that informed the design of the teaching experiment and 2) present a comparative case study analysis of two groups in the fourth-grade classroom. I found three student strategies that facilitated collaborative disciplinary decision making during the engineering design challenge: talking about plans, responsive discussion, and naming. These strategies further characterize the ways elementary students engage in engineering and reinforce the importance of argumentation as a skill and a practice for young engineering learners.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Kristen Wendell.; Committee: Chris Rogers, and David Hammer.; Keywords: Engineering, Education, and Elementary education.